Review of Euthanasia as a Therapy in Terminal Condition from Health and Law Perspective - Widiasa, Anak Agung Made; Nyoman Suyatna; Hartawan, I Gusti Agung Gede Utara (Babali Publisher, 2024)
Introduction: Terminal conditions and their treatment processes initiate actions that can be taken to relieve patients of the pain they suffer. This action is carried out by accelerating the death of patients with terminal conditions, known as euthanasia. Euthanasia is still being debated regarding the legal aspects and purpose of the act as part of the patient's treatment. This study aims to determine the perspective of euthanasia as part of the treatment or therapy of terminal conditions. Methods: This research is a literature study from several databases, including Proquest, Science Direct, SpringerLink, and Google Scholar. The article search used keywords combined with booleans. 755 articles were found according to the keywords, and 12 articles were selected using Prism analysis. Results: Euthanasia is seen as a way for terminal patients who have been resistant to treatment to be free from the misery of their illness. Euthanasia in health can be carried out if it is the patient's conscious choice without coercion and has met the medical requirements. Euthanasia can be carried out in areas, regions, or countries where there are regulations, laws, or similar regulations governing the implementation of euthanasia. Conclution: With the existence of clear rules for the implementation of euthanasia, health workers or families involved in euthanasia can provide a clear understanding of how to implement euthanasia.